TATA KELOLA SEKOLAH RSBI SERTA DAMPAKNYA TERHADAP KEPUASAN DAN LOYALITAS MASYARAKAT - Trismanto, Trismanto; Adiwijaya, Zainal Alim (Fakultas Ekonomi, Universitas Negeri Semarang, 2012)
The purpose of this study is getting a good model of school management of RSBI in Semarang. Societyâs satisfaction and loyalty mostly is determined by transparency, school accountability, and other factors such as, international standardization, academic effectiveness and funding effectiveness at RSBI. The population of this study were all RSBI students and parents in Semarang.Â The samples were taken by purposive sampling which the samples were taken based on a certain criteria and relevant to the purpose of this research. The data were collected by questionnaires and depth interview. Then, the data were analyzed by descriptive analysis approach to know the important and dominant factors in managing a good RSBI. Furthermore, Partial Least Square analysis (PLS) was used to know the influence of RSBI management (information transparency, school accountability, and other factors) toward societyâs satisfaction and loyalty in Semarang.Â